The features of the biennial shoot systems of Ulmus glabra Huds. characteristic of the crown in the virginal age state - Televinova Maria (EDP Sciences, 2021)
The morphological features of crowns were studied on the material of individuals of U. glabra of seed regeneration in the gaps of decaying three-hundred-year-old oak forests. We collected data on all crown shoots of five trees of young virginal age (from 10 to 18 years). The principal component method was used twice: first on the model tree to characterize features of the shoots biennial systems under the study, then to reveal ontogenetic and structural features of the crown organization of five virginal trees. Using the method of shoots biennial systems extraction allowed us to form a set of qualitative and quantitative characters reflecting crown structure properties of virginal trees of U. glabra, namely: properties of axes branching order, ontogenetic age of shoots in the crown, crown density, individual properties of tree crown structure.